The cost analysis of corrosion protection solutions for steel components in terms of the object life cycle cost = Analiza kosztów rozwiązań zabezpieczenia antykorozyjnego na stalowych elementach barier mostowych w kontekście życia obiektu - Kowalski, Dariusz; Grzyl, Beata; Kristowski, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Steel materials, due to their numerous advantages - high availability, easiness of processing and possibility of almost any shaping are commonly applied in construction for carrying out basic carrier systems and auxiliary structures. However, the major disadvantage of this material is its high corrosion susceptibility, which depends strictly on the local conditions of the facility and the applied type of corrosion protection system.
Keywords: anticorrosion protection; life cycle cost (LCC); steel material; LCC analysis; zabezpieczenie antykorozyjne; LCC; elementy stalowe; metody analizy LCC; koszty całkowite; bariera stalowa